The Supreme Court, race, and civil rights - Davis, Abraham L.; Graham, Barbara Luck.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1995)
Providing an overview of the Supreme Court and its rulings with regard to issues of equality and civil rights this text brings law, political science and history into the discussion of civil rights and the Supreme Court and incorporates the politically disadvantaged and the human component into the discussion.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Race discrimination -- Law and legislation -- United States; Civil rights -- United States; United States. -- Supreme Court; Electronic books